2013
DOI: 10.1063/1.4833563
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the ultrafast nonradiative deactivation mechanisms of thymine in aqueous solution: Excited-state QM/MM molecular dynamics simulations

Abstract: On-the-fly excited-state quantum mechanics/molecular mechanics molecular dynamics (QM/MM-MD) simulations of thymine in aqueous solution are performed to investigate the role of solvent water molecules on the nonradiative deactivation process. The complete active space second-order perturbation theory (CASPT2) method is employed for a thymine molecule as the QM part in order to provide a reliable description of the excited-state potential energies. It is found that, in addition to the previously reported deacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 51 publications
(107 reference statements)
4
71
0
Order By: Relevance
“…Regarding the new minimum identified in this section, 1 (ππ*) twisted-min , C6-C5 and C5-C7 bond distances are~1.45 and~1.49 Å, respectively. The CASPT2 method has additionally been benchmarked against MS-CASPT2 (see Table 2), a technique used previously to tackle the photochemical behavior of thymine [32,34,41]. The results here obtained are rather homogeneous, yielding similar estimates at both levels of theory.…”
Section: Type Of Calculationmentioning
confidence: 51%
See 1 more Smart Citation
“…Regarding the new minimum identified in this section, 1 (ππ*) twisted-min , C6-C5 and C5-C7 bond distances are~1.45 and~1.49 Å, respectively. The CASPT2 method has additionally been benchmarked against MS-CASPT2 (see Table 2), a technique used previously to tackle the photochemical behavior of thymine [32,34,41]. The results here obtained are rather homogeneous, yielding similar estimates at both levels of theory.…”
Section: Type Of Calculationmentioning
confidence: 51%
“…Both static [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and dynamic [16,17,[35][36][37][38][39][40][41] theoretical studies have been performed over the last decade, the former usually employing more accurate and correlated methods due to their lower computational cost. Multiconfigurational methods are usually the preferred choice, particularly the complete active space self-consistent field (CASSCF) [42] and its second-order perturbation theory extension (CASPT2) [43].…”
Section: Introductionmentioning
confidence: 99%
“…A obvious step further is completeactive-space perturbation theory (e.g., CASPT2 [190] ), which offers very good accuracy (oftentimes better than MRCI) and performance (usually much faster than MRCI). Few surface hopping studies based on CASPT2 have been reported already, [191][192][193][194] albeit no ISC dynamics simulation has been published until now, as no current implementation of CASPT2 can provide all necessary quantities. Other promising electronic structure methods are, for example, the approximately size-consistent MRCI variant linear-response-theory multireference average-quadratic coupled-cluster (LRT-MRAQCC) [177] or density matrix normalization group (DMRG) approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The most important difference lies in the disappearance of the CO stretch mode for thymine and M24PDA, and the appearance of the strong CO stretch mode for uracil, MTCA and 3M3P2O. To our understanding, the disappearance of the CO stretch mode of thymine in water or M24PDA is mostly due to the out‐of‐plane distortion motion of the CCCO motif occurring suddenly in the Franck–Condon region, if keep in mind that the structure of S 2 (ππ*)/S 0 CI for thymine or S 2 (ππ*)/S 1 CI for M24PDA is severely distorted and that the S 2 (ππ*) → S 0 internal conversion via S 2 (ππ*)/S 0 CI is the predominant channel (~90% population) for thymine. We thus speculate that the very high efficiency of the S 2 (ππ*) → S 0 internal conversion for thymine in water is mostly due to the predominant wave‐packets motion towards the S 2 (ππ*)/S 0 in the Franck–Condon region.…”
Section: Resultsmentioning
confidence: 94%